ENVIRONMENTAL PROTECTION FROM THE PERSPECTIVES OF INDONESIAN, SUFI AND UNITED KINGDOM MUSLIM ENVIRONMENTALISTS - Irawan, Bambang (Center for Research and Development of Religious Literature and Heritage, 2016)
The challenge posed by the world’s current environmental crisis has elicited a response from mainstream world religions in the form of efforts to construct a system of environmental ethics, based on religious and spiritual values. Suggestions for protecting and conserving the environment are a very ancient and fundamental aspects of religious teaching. The author will explore the perspectives of a number of environmental thinkers: Fachruddin Mangunjaya of Indonesia, Hossein Nasr (as representative of Sufism), and Fazlun Khalid of the United Kingdom. The paper well go on to identify a number of different approaches that offer some measure of environmental protection and I will draw on structured and unstructured interviews with these thinkers in order to further explore their published works on nature conservation. From these sources, the author discovers an urgent need for religious communities to engage in the work of sustaining this planet. The author has also identified the means to utilize and empower religious doctrines for environmental conservation. From these three sources, we can learn strategies for elaborating productive Islamic values of environmental conservation and promoting a greater need of engagement and collaboration among them in initiating practical conservation projects.